Financial Ratios Analysis Using The Z-Score Altman Method In Measuring Financial Performance To Predict Bankruptcy In Sharia General Banking (Case Study Of Islamic Banking Companies Listed On The Indonesia Stock Exchange In 2020-2021) - Eka Ayu Anggraini; Hartono; Yuliasnita Verlandes (International Journal of Management and Business Economics, 2023)
This study aims to predict the potential level of corporate bankruptcy. In this study, researchers took the object of Islamic banking companies listed on the Indonesian Stock Exchange. The companies are as follows: PT. Bank Aladin Syariah Tbk, PT. Bank Syariah Indonesia Tbk, PT. Bank BTPN Syariah Tbk and PT. Bank Panin Dubai Syariah Tbk. This type of research uses descriptive quantitative using secondary data sources.The results of the study show that 2020-2021 shows healthy and stable results because the z-score for 2020-2021 is above 2.6 or Z-score > 2.6. That's why PT. Bank Aladin Syariah Tbk, PT. Bank Syariah Indonesia Tbk, PT. Bank BTPN Syariah Tbk and PT. Bank Panin Dubai Syariah Tbk must continue to apply the precautionary principle properly and continue to strive to improve the company's performance in order to avoid potential bankruptcy in the coming year, especially in the era of economic improvement after the Covid-19 pandemic